2013
DOI: 10.1098/rspb.2012.2821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating factors that predict the structure of a commensalistic epiphyte–phorophyte network

Abstract: A central issue in ecology is the understanding of the establishment of biotic interactions. We studied the factors that affect the assembly of the commensalistic interactions between vascular epiphytes and their host plants. We used an analytical approach that considers all individuals and species of epiphytic bromeliads and woody hosts and non-hosts at study plots. We built models of interaction probabilities among species to assess if host traits and abundance and spatial overlap of species predict the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 67 publications
10
107
2
Order By: Relevance
“…All rights reserved. epiphytes and their hosts is considered a commensalistic relationship (Benzing and Seeman, 1978;Sáyago et al, 2013) or a facilitative interaction system (Callaway et al, 2002). Nevertheless, some epiphytic species can act as "structural parasites" (Stevens, 1987) because they can cause adverse effects in the host tree, such as defoliation and branch-death (Benzing and Seeman, 1978;Benzing, 2008;Caldiz and Beltrano, 1989;Johansson, 1974;Ruinen, 1953).…”
Section: Introductionmentioning
confidence: 96%
“…All rights reserved. epiphytes and their hosts is considered a commensalistic relationship (Benzing and Seeman, 1978;Sáyago et al, 2013) or a facilitative interaction system (Callaway et al, 2002). Nevertheless, some epiphytic species can act as "structural parasites" (Stevens, 1987) because they can cause adverse effects in the host tree, such as defoliation and branch-death (Benzing and Seeman, 1978;Benzing, 2008;Caldiz and Beltrano, 1989;Johansson, 1974;Ruinen, 1953).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have found that species abundance has a major role in determining how interactions are structured in different ecological networks, including positive interactions such as plant-pollinators [9,14] and plant-plant facilitation [15], commensalistic interaction among epiphytes and phorophytes [16] or antagonisms between plant-herbivores and hosts-parasitoids [12,17]. These studies also showed that the observed interactions are better predicted by simulations when other factors are included together with the abundance, such as phenological overlap [9,11,12], morphological matches among species [14] or the phylogenetic relationship, which ultimately influences the traits of the species [15].…”
Section: Introductionmentioning
confidence: 99%
“…Epiphyte colonization depends on the conditions and support provided by the host tree; therefore, epiphytes can be considered useful biological indicators of ecosystem health (Hayasaka et al 2012, Sáyago et al 2013. We can predict a rich bromeliad flora in mangroves with good development and conservation status, especially in mangrove forests with great abundance of mature specimens of L. racemosa.…”
Section: Discussionmentioning
confidence: 99%